Pengaruh Kemampuan Analisis terhadap Prestasi Belajar Matematika Ditinjau dari Intellegent Quotion (IQ) - Agus Setiawan (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2017)
The objective of this study was to investigate the effect of analytical on learning achievement viewed from IQ. This research used the causal comparative research with the factorial design of 3 x 3. Its population was all of the students of mathematics education in Islamic Institute Of Ma’arif NU Metro Lampung. The samples of the research were taken by using the random sampling. The instruments used to gather the data of the research were test of learning achievement in Mathematics, test of analytical individu and test of IQ of the students. Prior to their use, both the test were tried out. Their contents were validated by the related experts. The reliability of the instruments was tested by using the Cronbach Alpha formula. The discrimination power of the test and the internal consistency of the questionnaire used Karl Pearson’s product moment correlation formula. The pre-requisite tests of the research included the normality test by using Lilliefors test and homogeneity test by using Bartlett test. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research are as follows. 1) The students with high IQ have a better learning achievement in Mathematics than students with moderate IQ. 2) The students with the high analytical individu have a better learning achievement in Mathematics than those with the moderate and low analytical individu, and the students with the moderate analytical individu have a better learning achievement in Mathematics than those with the low analytical individu. 3) There was interaction among analytical and IQ on learning achievement mathematics.